2011
DOI: 10.1007/s10156-010-0187-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of the 2009 swine-origin influenza A (H1N1) outbreak in Japan

Abstract: To clarify the clinical symptoms of the influenza A virus during the 2009 pandemic influenza outbreak, we describe the clinical features of outpatients diagnosed with type A influenza by use of the rapid influenza diagnostic test (RIDT) from September to December 2009. Questionnaires were used to collect prospective data on 1,122 cases with influenza-like illness at our medical institutions. The independent predictors of influenza A virus were identified on the basis of demographic features and the clinical sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
2
8
0
Order By: Relevance
“…With regards to age distribution in our study, the A(H1N1)pdm09-infected patients were younger than seasonal influenza patients. This result was consistent with previous reports from China (20) as well as other countries (24,26) such as Japan (32). The data discussed above suggests that A(H1N1)pdm09 infections appear to show seasonal variations in different climate zones but display universally similar clinical features.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…With regards to age distribution in our study, the A(H1N1)pdm09-infected patients were younger than seasonal influenza patients. This result was consistent with previous reports from China (20) as well as other countries (24,26) such as Japan (32). The data discussed above suggests that A(H1N1)pdm09 infections appear to show seasonal variations in different climate zones but display universally similar clinical features.…”
Section: Discussionsupporting
confidence: 82%
“…In our present study, A(H1N1)pdm09-infected adolescent cases had a higher rate of contact with infected individuals, and a sharp rise in prevalence was observed after the new semester of school started at EW 36. Another possibility is that older people may have cross-immunoreactivity (32)(33)(34)(35) or long-term T cell-mediated immunity (36) against A(H1N1)pdm09, as a result of prior exposure to influenza virus that was genetically and antigenically closely related to the A(H1N1)pdm09 strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of both these symptoms were lower than those reported by Dawood et al (25% for each symptom), 9 but higher than those reported in other studies. 21,22 In a comparison between patients infected with pandemic H1N1 (2009) influenza and those infected with seasonal influenza, Carcione et al identified diarrhea as a significant variable distinguishing H1N1-infected patients. 13 However, a study from Singapore did not confirm the same finding.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 The aggressive use of antiviral agents resulted in milder disease activity and the lowered the mortality. 14 In the Niigata Prefecture specifically, variations in H1N1 pdm09 infection were different from those in the whole of Japan. The case numbers reported as H1N1 pdm09 infection (!…”
Section: Introductionmentioning
confidence: 98%